Response of piping system with semi-active variable friction dampers under tri-directional seismic excitation. (1st January 2013) - Kumar, Praveen; Jangid, R.S.; Reddy, G.R.
Seismic loads on piping system due to earthquakes can cause excessive vibrations, which can lead to serious instability resulting in damage or complete failure. In this paper, semi-active variable friction dampers (SAVFDs) have been studied to mitigate seismic response and vibration control of piping system used in the process industries, fossil and fissile fuel power plant. A study is also conducted on the performance of control due to variation in gain multiplier (a) in the present control law, which plays an important role in the present control algorithm of the damper. The effectiveness of the SAVFD in terms of reduction in the responses, namely, displacements, accelerations and base shear of the piping system is investigated by comparing uncontrolled responses under four artificial earthquake motions with increasing amplitudes. The analytical results demonstrate that the SAVFDs under particular optimum parameters are very effective and practically implementable for the seismic response mitigation, vibration control and seismic requalification of piping systems.